2017
DOI: 10.1007/s00425-017-2687-7
|View full text |Cite
|
Sign up to set email alerts
|

In Brachypodium a complex signaling is actuated to protect cells from proteotoxic stress and facilitate seed filling

Abstract: A conserved UPR machinery is required for Brachypodium ER stress resistance and grain filling. Human and livestock diets depend on the accumulation of cereal storage proteins and carbohydrates, including mixed-linkage glucan (MLG), in the endosperm during seed development. Storage proteins and proteins responsible for the production of carbohydrates are synthesized in the endoplasmic reticulum (ER). Unfavorable conditions during growth that hamper the ER biosynthetic capacity, such as heat, can cause a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Leaves from 8‐week‐old plants were ground in liquid nitrogen using a mortar and pestle. Protein preparation and detection of protein were followed as described previously (Kim et al ., ). Anti‐GFP serum (Abcam, http://www.abcam.com) was used at a 1:3000 dilution.…”
Section: Methodsmentioning
confidence: 97%
“…Leaves from 8‐week‐old plants were ground in liquid nitrogen using a mortar and pestle. Protein preparation and detection of protein were followed as described previously (Kim et al ., ). Anti‐GFP serum (Abcam, http://www.abcam.com) was used at a 1:3000 dilution.…”
Section: Methodsmentioning
confidence: 97%
“…Thus, these studies indicated that, in general, the synthesis of storage proteins during normal seed development may challenge the protein folding capacity of the ER. Direct correlation with UPR signaling was indicated by the increase in both bZIP60 expression and unconventional splicing when synthesis of storage proteins is active in the endosperm of maize ( Gayral et al, 2017 ) and of Brachypodium distachyon , a grass evolutionarily close to wheat and barley ( Kim et al, 2017 ).…”
Section: Seed Storage Protein Classes and Bip Interactionsmentioning
confidence: 99%
“…Increased temperatures beyond physiological levels is perhaps the most serious abiotic insult encountered by crops. In Brachypodium distachyon , measurements in developing endosperm showed increases of one BiP and one PDI transcript and both spliced and unspliced bZIP60 at early developmental stages, when storage protein synthesis is particularly high, compared to other plant tissues ( Kim et al, 2017 ). Mild heat stress (30°C) did not further increase BiP and PDI transcripts that are induced during seed development, and actually decreased those of the two chaperones ( Kim et al, 2017 ).…”
Section: Upr and Seed Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…One arm consists of the most conserved ER stress sensor IRE1, which mediates cytoplasmic splicing of bZIP60 mRNA and RIDD (Deng et al 2011;Mishiba et al 2013;Nagashima et al 2011). Cytoplasmic splicing in plants was first reported in Arabidopsis bZIP60, and was experimentally verified also in other flowering plants such as rice, maize, and Brachypodium (Hayashi et al 2012;Kim et al 2017;Li et al 2012). bZIP60 mRNA encodes a bZIP domain followed by a transmembrane domain, which anchors bZIP60 proteins on the ER membrane.…”
Section: Introductionmentioning
confidence: 99%